Fasting-sensitive SUMO-switch on Prox1 controls hepatic cholesterol metabolism - Alfaro Nunez, Ana Jimena; Dittner, Claudia; Becker, Janina; Loft, Anne; Mhamane, Amit; Maida, Adriano; Georgiadi, Anastasia; Tsokanos, Foivos Filippos; Klepac, Katarina; Molocea, Claudia-Eveline; El Merahbi, Rabih; Motzler, Karsten; et al. (EMBO reports, 2023)
Abstract Accumulation of excess nutrients hampers proper liver function and is linked to nonalcoholic fatty liver disease (NAFLD) in obesity. However, the signals responsible for an impaired adaptation of hepatocytes to obesogenic dietary cues remain still largely unknown. Post-translational modification by the small ubiquitin-like modifier (SUMO) allows for a dynamic regulation of numerous processes including transcriptional reprogramming. We demonstrate that specific SUMOylation of transcription factor Prox1 represents a nutrient-sensitive determinant of hepatic fasting metabolism. Prox1 is highly SUMOylated on lysine 556 in the liver of ad libitum and refed mice, while this modification is abolished upon fasting. In the context of diet-induced obesity, Prox1 SUMOylation becomes less sensitive to fasting cues. The hepatocyte-selective knock-in of a SUMOylation-deficient Prox1 mutant into mice fed a high-fat/high-fructose diet leads to a reduction of systemic cholesterol levels, associated with the induction of liver bile acid detoxifying pathways during fasting. The generation of tools to maintain the nutrient-sensitive SUMO-switch on Prox1 may thus contribute to the development of ?fasting-based? approaches for the preservation of metabolic health.
Gesehen am 17.08.2023